Cluster analysis of Sumatra Island earthquake distribution - Anggraini, Dian; Indratno, Sapto Wahyu; Mukhaiyar, Utriweni; Puspito, Antonius Nanang T. (Desimal: Jurnal Matematika, 2024)
Sumatra Island is highly vulnerable to earthquakes due to multiple seismic sources, including megathrusts, faults, and volcanic activities spanning from Aceh to Lampung. The International Seismological Centre (ISC) has recorded 9,414 earthquakes in Sumatra with magnitudes ranging from 4.0 to 9.1 since 1907. Insufficient preparedness in responding to sudden earthquakes challenges local and central governments in managing impacts. To address this, a risk classification of earthquake-prone areas was conducted using cluster analysis. The "K-means cluster" method identified five earthquake clusters in Sumatra. Cluster 4 has the most events (3,787) but with generally lower magnitudes, resulting in minimal damage. Cluster 2, however, is more concerning due to shallow earthquakes from subduction zones, faults, and volcanoes. This clustering analysis provides critical information for government planning in earthquake risk mitigation and preparedness.